IMPLEMENTASI ZAKAT OLEH BAZNAS YOGYAKARTA DALAM PERSPEKTIF HADIS - Luthfi Hidayah Nur'aini (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study examines the implementation of zakat by the National Zakat Agency (BAZNAS) Yogyakarta from the perspective of hadith. Zakat is an obligation in Islam that plays a crucial role in wealth distribution and social welfare. BAZNAS Yogyakarta, as an official institution, is responsible for managing, collecting, and distributing zakat funds to ensure they are allocated appropriately according to Islamic principles. This research employs a qualitative method with a descriptive-analytical approach, utilizing literature studies and hadith analysis related to zakat. The findings indicate that BAZNAS Yogyakarta has implemented zakat principles as taught in hadith, particularly in aspects of transparency, fair distribution, and mustahik (zakat recipient) empowerment. Various social and economic programs run by BAZNAS, such as assistance for the poor, educational scholarships, healthcare services, and productive business capital, reflect optimal efforts to utilize zakat for community welfare. Additionally, this study highlights challenges faced by BAZNAS Yogyakarta, including increasing public trust and improving the effectiveness of zakat fund management. In conclusion, zakat implementation based on hadith can enhance the effectiveness of zakat management and ensure its benefits are widely felt by society, particularly in improving welfare and reducing economic disparities.